Front Cover: cyc‐DEP: Cyclic immunofluorescence profiling of particles collected using dielectrophoresis. Issue 16 (1st September 2022) - Gustafson, Kyle T.; Sayar, Zeynep; Le, Hillary; Gustafson, Steven L.; Gower, Austin; Modestino, Augusta; Ibsen, Stuart; Heller, Michael J.; Esener, Sadik; Eksi, Sebnem E.
Abstract : DOI: 10.1002/elps.202200001 The cover picture shows the collection of endogenous nanoparticles from blood using a dielectrophoretic chip that consists of a planar microelectrode array. Downstream immunolabeling reveals the diverse proteomic content of captured particles, represented by a spectrum of colors fluorescing at collection regions on the chip. Our group developed a technique called "cyc‐DEP" to improve the multiplicity of on‐chip proteomic analysis in what we believe is the first application of cyclic immunofluorescence for profiling liquid biopsies. Techniques like cyc‐DEP showcase the potential utility of low‐volume, minimally‐invasive, lab‐on‐a‐chip platforms for patient stratification in routine screening and early disease detection.